2021
DOI: 10.7759/cureus.12988
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Procalcitonin Levels for Diagnosis of Culture-Positive Sepsis in Critically Ill Trauma Patients: A Retrospective Analysis

Abstract: Background Abdominal trauma and intra-abdominal sepsis are associated with significant morbidity and mortality. Microcirculation in the gut is disrupted in hemorrhagic and septic shock leading to tissue hypoxia, and the damaged gut acts as a reservoir rich in inflammatory mediators and provides a continual source of inflammation to the systemic circulation leading to sepsis. Sepsis is defined as the presence (probable or documented) of infection together with a systemic inflammatory response to infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Some studies have indicated that sepsis patients with elevated PCT levels have a higher mortality rate than patients with decreased PCT levels ( 21 23 ). Bakhtiar et al ( 24 ) found that PCT was significantly higher in culture-positive sepsis than in culture-negative sepsis. In our study, PCT in the CPSS group was significantly higher than that in the CNSS group.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that sepsis patients with elevated PCT levels have a higher mortality rate than patients with decreased PCT levels ( 21 23 ). Bakhtiar et al ( 24 ) found that PCT was significantly higher in culture-positive sepsis than in culture-negative sepsis. In our study, PCT in the CPSS group was significantly higher than that in the CNSS group.…”
Section: Discussionmentioning
confidence: 99%
“…Considering IAI is associated with increased levels of proinflammatory cytokines [6], and to obtained significant difference between levels estimated before and after infusion, sample size was calculated to include >60 patients per group to get a study power of 80% with α cutoff point of 0.05 and β cutoff point of 0.2.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…Meckel's diverticulum is a congenital malformation that can be complicated with intestinal obstruction, diverticulitis or perforation [5]. In general, intra-abdominal sepsis causes disruption of gut microcirculation with subsequent tissue hypoxia, and the damaged gut acts as reservoir for inflammatory mediators and provides a continual source of these mediators to the systemic circulation [6].…”
Section: Introductionmentioning
confidence: 99%